2020
DOI: 10.1108/ijem-08-2018-0231
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge hiding, conscientiousness, loneliness and affective commitment: a moderated mediation model

Abstract: PurposeThis paper examines the detrimental effects of perceived knowledge hiding (KH) on loneliness and affective commitment within academic settings. It further investigates the influence of conscientiousness as a moderator.Design/methodology/approachUsing the cross-sectional survey methodology, the proposed moderated mediation model has empirically tested the effect of perceived KH on a sample of 300 students pursuing management education at a premier institute in India.FindingsThe findings reveal that perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 106 publications
(150 reference statements)
2
33
1
Order By: Relevance
“…The study also found a direct positive and desirable consequence associated with performing KH behavior and academic performance warrants looking into from the creation of indirect distrust loops among the cohort (Garg and Anand, 2020;Cerne et al, 2014). To suppress such undesired behavior, managers and academics need to devise interventions aiming at behavioral changes (Daniels, 2016) such as environment creation for more sharing-based assignments and submission.…”
Section: Practical Implications Of the Studymentioning
confidence: 98%
See 4 more Smart Citations
“…The study also found a direct positive and desirable consequence associated with performing KH behavior and academic performance warrants looking into from the creation of indirect distrust loops among the cohort (Garg and Anand, 2020;Cerne et al, 2014). To suppress such undesired behavior, managers and academics need to devise interventions aiming at behavioral changes (Daniels, 2016) such as environment creation for more sharing-based assignments and submission.…”
Section: Practical Implications Of the Studymentioning
confidence: 98%
“…KH is reported to inhibit cooperative exchange among students leading to deterioration of their interpersonal relationships (Gillies, 2014), team creativity (Bari et al, 2019) and giving rise to feeling of loneliness as well as reduced affective commitment toward the academic institution (Garg and Anand, 2020). In knowledge-intensive organizations, such as academic institutions, acts of KH may defeat the purpose of the existence of academic institutions altogether.…”
Section: Literature Review and Hypotheses Buildingmentioning
confidence: 99%
See 3 more Smart Citations